1996
DOI: 10.1108/eb022604
|View full text |Cite
|
Sign up to set email alerts
|

Socially responsible behaviour: values and attitudes of the alternative trading organisation consumer

Abstract: The purpose of this study was to examine whether consumers' intentions to purchase apparel products from an alternative trading organisation (ATO; an example of socially responsible consumer behaviour) could be explained by their societally‐centred values and attitudes, as well as attitudes more specifically related to purchasing. Data were collected with a nationwide mail survey of US consumers (n =344) randomly drawn from the stratified mailing list of one North American ATO. Theory‐based relationships, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 23 publications
6
65
0
2
Order By: Relevance
“…This supposition is supported by Dickson and Littrell (1996) who also distinguished dual pathways leading to purchase, one attitude towards the behaviour of purchasing ethical clothing and the other attitude towards the clothing itself. Thus, for many consumers both a wider ethical attitude and narrower product attributes contribute to purchasing behaviour, a finding supported by the separation of the dominant pathways in the HVM.…”
Section: Motivational Incongruencies and Value Trade-offsmentioning
confidence: 83%
See 3 more Smart Citations
“…This supposition is supported by Dickson and Littrell (1996) who also distinguished dual pathways leading to purchase, one attitude towards the behaviour of purchasing ethical clothing and the other attitude towards the clothing itself. Thus, for many consumers both a wider ethical attitude and narrower product attributes contribute to purchasing behaviour, a finding supported by the separation of the dominant pathways in the HVM.…”
Section: Motivational Incongruencies and Value Trade-offsmentioning
confidence: 83%
“…For example, Joergens (2006) and Iwanow et al (2005), in studies of all clothing consumers, conclude that price, style and quality are the primary influence on clothes purchase, ethical considerations are of secondary importance. In contrast, Sneddon, Lee & Soutar (2009) and Dickson & Littrell (1996) (Shaw et al 2006). Ethical clothing consumers may also search to express their ideology and self-identity through their clothing, i.e., egoistic motives (Niinimäki 2010).…”
Section: Ethical Clothing Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a cognitive standpoint, consumers want their attitudes to be consistent with their behavior (Eagly and Chaiken, 1993). In terms of socially responsible buying behavior, researchers (Dickson and Littrell, 1996;Kim, Littrell, and Ogle, 1999) have found that individuals who purchase products from alternative trade organizations tend to have positive attitudes toward behaving ethically in the marketplace. Extrapolating from these findings, it is expected that individuals who purchased rubber charity bracelets had a more positive attitude toward ethical consumption than those who did not buy the bracelets.…”
Section: Literature Reviewmentioning
confidence: 99%